The Efficiency of Requesting Process for Formal Business-Documents in Indonesia: An Implementation of Web Application Base on Secure and Encrypted Sharing Process - Setyawan, Aris Budi; Tarigan, Avinanta; Sussanto, Herry (School of Business and Management Institut Teknologi Bandung, 2014)
In recent business practices, the need of the formal document for business, such as the business license documents, business domicile letters, halal certificates, and other formal documents, is desperately needed and becomes its own problems for businesses, especially for small and medium enterprises. One stop service unit that was conceived and implemented by the government today, has not been fully integrated yet. Not all permits (related with formal document for business) can be completed and finished in one place, businesses are still have to move from one government department to another government department to get a formal document for their business. With these practices, not only a lot of the time and cost will be sacrificed, but also businesses must always fill out a form with the same field. This study aims to assess and identify the problem, especially on applying the formal document for business, and use it as inputs for the development of a web application based on secure and encrypted sharing process. The study starts with a survey of 200 businesses that have applied the formal document for their business, to map the initial conditions of applying the formal document for business in Indonesia . With these applications that are built based on these needs, it is expected that not only the time, cost, and physical effort from both parties are becoming more efficient, but also the negative practices of bureaucratic and economic obstacles in business activities can be minimized, so the competitiveness of business and their contribution for national economy will increase.Keywords : Formal documents, Efficiencies, Web application, Secure and encrypted sharing process, SMEs